Miscibility in two phase-separated binary self-assembled monolayers composed of hydrophilic components on Au(111) - Phong, Pham Hong (Vietnam Journal of Chemistry, 2017)
The typical characteristic of two binary self-assembled monolayer (SAMs) composed of 11-aminoundecanethiol hydrochloride (AUT), and 10-carboxy-1-decanethiol (MUA) in each and the other was 2-hydroxylethanethiol (MeOH) was investigated. The dependence of charges (Q), estimated from the peak areas in cyclic voltammograms on the mixing ratios of components (csolMeOH) indicated that QMUA = QMeOH at csolMeOH = 0.8, meanwhile QAUT = QMeOH at csolMeOH = 0.5, suggesting that adsorbed MUA molecules prevented the adsorption of MeOH molecules. Fourier transform infrared spectrometry (FTIR) showed the increase of band at 2855 cm-1 and 2965 cm-1, assigned to symmetric and asymmetric of CH2, respectively, of SAM of AUT, indicating the more perpendicular orientation of AUT molecules compared with MUA molecules on the Au(111) surface. This result interpreted the degree of phase separation in binary SAMs of AUT-MeOH compared with binary SAMs of MUA-MeOH. Keywords. Binary self-assembled monolayers, miscibility, hydrophilic components.